Enhancement of power generation of thermoelectric generator using phase change material. Issue 1 (July 2020) - Mao, Jianhui; Liu, Anbang; Wang, Yuanyuan; Li, Yihuai; Xie, Huaqing; Wu, Zihua
Abstract: This paper demonstrates a thermoelectric generator (TEG) that embeds phase change material (PCM) for waste heat energy harvesting. In this TEG module, a volume of molten carbonate salt is encapsulated in a cuboid polydimethylsiloxane (PDMS) body. In order to study the effect of embedded PCM on the TEG performance, we compared the performance of TEGs with and without PCM. The results show that a higher output voltage and a longer energy harvesting time can be reached in TEG with PCM in compared with the corresponding values in the TEG without PCM once the heat source stops supplying heat. Especially, the relative increase of the total electricity by adopting the PCM is as large as 25%. Our work proposes an effective and feasible way to enhance the performance of the TEG system by application of the PCM.